Efektivitas Penggunaan Modul Kesetimbangan Ion dan pH Larutan Garam Berbasis Inkuiri Terbimbing Terhadap Hasil Belajar Peserta Didik Kelas XI SMA Negeri 13 Padang - Faizah Az Zahra; Iryani Iryani (Edukimia, 2022)
This research aims to determine the effectiveness of using guided inquiry-based ion equilibrium and pH of salt solution modules on students learning outcomes. This module has been tested for validity and practicality, but the effectiveness has not been tested. This study is using the pre-experimental method with pretest and posttest questions as the research instrument. The increased score of the student has a homogeneous variance and normally distributed. Based on the paired t-test at a 0,05 significant level, obtained t-count (62.29) score is bigger than t-table (2.73) score, which showed an improvement in student learning outcomes. The N-gain was conducted based on the student learning outcomes and had a value of 0.597, categorized as moderate. Thus, this module effectively improve student learning outcomes.